2009
DOI: 10.1074/jbc.m807151200
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal Serine Protease CLN2 Regulates Tumor Necrosis Factor-α-mediated Apoptosis in a Bid-dependent Manner

Abstract: Apoptosis is a highly organized, energy-dependent program by which multicellular organisms eliminate damaged, superfluous, and potentially harmful cells. Although caspases are the most prominent group of proteases involved in the apoptotic process, the role of lysosomes has only recently been unmasked. This study investigated the role of the lysosomal serine protease CLN2 in apoptosis. We report that cells isolated from patients affected with late infantile neuronal ceroid lipofuscinosis (LINCL) having a defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…Recently, accumulating evidences suggest the existence of a lysosomal pathway for apoptosis (Guicciardi et al, 2004). The lysosomal membrane permeabilization (LMP) that leads to the release of lysosomal proteases into the cytosol may initiate the apoptotic program in several models of apoptosis (Chwieralski et al, 2006;Stoka et al, 2007;Boya and Kroemer, 2008), such as TNFα-induced apoptosis (Autefage et al, 2009). Our studies revealed the first E3 ligase that localizes to lysosmes and exhibits proapoptotic activities at the same time.…”
Section: Discussionmentioning
confidence: 81%
“…Recently, accumulating evidences suggest the existence of a lysosomal pathway for apoptosis (Guicciardi et al, 2004). The lysosomal membrane permeabilization (LMP) that leads to the release of lysosomal proteases into the cytosol may initiate the apoptotic program in several models of apoptosis (Chwieralski et al, 2006;Stoka et al, 2007;Boya and Kroemer, 2008), such as TNFα-induced apoptosis (Autefage et al, 2009). Our studies revealed the first E3 ligase that localizes to lysosmes and exhibits proapoptotic activities at the same time.…”
Section: Discussionmentioning
confidence: 81%
“…However, the physiological functions of cathepsins have been controversial because the optimum pH for their enzymatic activities is acidic and they are usually autolyzed or denatured under the physiological conditions of the cytosol (pH 7.4) [8]. Thus, there might be other proteases, such as proteases with optimum pH at 7.4, that mediate apoptosis [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…As a lysosomal enzyme TPPI has been shown to participate in cell death (apoptosis or necrosis) following lysosomal membrane rupture and release of acid hydrolases in the cell cytosol. Fibroblasts deficient in TPPI activity cannot start tumor necrosis factor-induced apoptosis (Autefage et al, 2009). Moreover, TPPI can activate Bid throughout a proteolytic cleavage thus participating in the receptor-dependent apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Its genetically determined deficiency causes the late infantile neuronal ceroid lipofuscinosis (LINCL)-a recessive neurodegenerative disease leading to an early death of affected individuals (Mole et al, 2005). TPPI is shown to participate in receptor-mediated apoptosis throughout proteolytic cleavage of Bid in isolated fibroblasts (Autefage et al, 2009). On the other hand, it is demonstrated (Van Beersel et al, 2013) that TPPIdeficient fibroblasts exhibit an enhanced BNIP3 (Bcl2/adenovirus E1 B 19 kDa interacting protein 3) activation.…”
Section: Brain Regionmentioning
confidence: 98%